BL_GERICHTE 720 2013 172 / 39 vom 20. März 2001 , Entscheid des Kantonsgerichts Basel-Landschaft, Abteilung Sozialversicherungsrecht vom 6. Februar 2014 (720 13 172 / 39) - BL Gerichte (2001)
Hilflosenentschädigung